(untitled) (Kathmandu University Medical Journal, 2022)
Background Type 2 diabetes constitutes about 85-95% of all diabetes in developed countries, and accounts for an even higher percentage in developing countries. Diabetic retinopathy is probable the most characteristic, easily identifiable and treatable complication of diabetes, but remains an important cause of visual loss. Objective To study P100 latencies and inter ocular latency difference in diabetic group and compared it with a control group and study the correlation between P100 and inter ocular latency difference with the duration of disease in diabetic group. Method A comparative, cross sectional study was done from September 2016 to January 2018 in Neurophysiology Lab, Basic and Clinical Physiology, BP Koirala Institute of Health Sciences. The sample size was 64 and random sampling technique was used. Subjects were divided into three groups according to the duration of disease. Anthropometric and visual evoked potentials were recorded. Descriptive analysis, analysis of covariance and Post Hoc multiple comparison analyses were done using SPSS 11.5. Pearson’s correlation was applied between P100 latency and inter ocular latency difference with the duration of disease. Result On using analysis of covariance, P100 latencies were significantly prolonged in diabetic as compared to healthy controls (p < 0.001). Post Hoc multiple comparison showed significant differences in both left and right P100 latencies within diabetic groups and between diabetic groups and healthy controls. Left inter ocular latency difference showed positive correlation with the duration of disease. Conclusion P100 latencies are significantly prolonged in diabetes patients and is positively correlated with duration of disease. Visual evoked potential test can be useful for detecting retinal dysfunction before the appearance of symptoms of retinopathy.